2016
DOI: 10.2528/pierc16042105
|View full text |Cite
|
Sign up to set email alerts
|

Broadband Flat Gain Enhancement of Planar Double-Dipole Quasi-Yagi Antenna Using Multiple Directors

Abstract: Abstract-In this article, a method of broadband flat gain enhancement for a planar double-dipole quasi-Yagi antenna using multiple directors is proposed. The proposed antenna consists of two dipole drivers with different lengths, a truncated ground plane, and three parasitic strip directors. First, the length ratio of the two dipoles is adjusted to increase the gain in the low-frequency region. Next, three parasitic strip directors are employed to increase the impedance bandwidth and improve the gain of the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…It is observed that the gain improvement of the proposed antenna is more than [22,23]. The proposed antenna configuration is laterally smaller than that in [21,22], whereas it is vertically smaller than that in [21,23]. Table 3.…”
Section: Results and Analysismentioning
confidence: 97%
“…It is observed that the gain improvement of the proposed antenna is more than [22,23]. The proposed antenna configuration is laterally smaller than that in [21,22], whereas it is vertically smaller than that in [21,23]. Table 3.…”
Section: Results and Analysismentioning
confidence: 97%
“…2 shows the resonant cavity antenna which is formed between these two planes. In this way, the distance between superstrate and ground plane is as follows [13]:…”
Section: Analysis and Physical Insightmentioning
confidence: 99%
“…In this design, a parasitic patch and windowed superstrate as a gain enhancement method are applied. A planar double-dipole quasi-Yagi antenna using multiple directors as a method of flat gain enhancement was reported in [13]. In [14] printed frequency scanning antenna based on an even-mode bilateral broadside-coupled suspended microstrip line was investigated.…”
Section: Introductionmentioning
confidence: 99%